Feasibility and safety of 3D-navigated trans-sacral bar osteosynthesis for fragility fractures of the sacrum: first clinical experiences - Regenbogen, Stephan; Barbari, Jan el; Vetter, Sven Y.; Franke, Jochen; Grützner, Paul Alfred; Swartman, Benedict (Journal of Clinical Medicine, 2024)
Background: There has been an increasing number of fragility fractures of the sacrum in the recent decade. With rates of up to 28%, the complication rates after surgical treatment are still at an unacceptably high level, and new treatment strategies are urgently needed. Therefore, the purpose of this study was to evaluate the potential of 3D-navigated trans-sacral bar osteosynthesis in the surgical treatment of fragility fractures of the sacrum. Methods: Retrospectively, from 2017 to 2023, all cases with confirmed fragility fractures of the sacrum in patients > 65 years of age that were surgically treated with navigated 3D-navigated trans-sacral bar osteosynthesis were included, and epidemiological data and the course of treatment analyzed in comparison to a matched control group. Results: Finally, 21 patients (18 women and 3 men) were included in this study. The average age of the patients was 82.6 (SD 6.3) in the intervention group and 79.4 (SD 6.7) in the control group. There were postoperatively detected complications in two cases (18%) in the intervention group and in four cases (40%, p = 0.362) in the control group. The postoperative in-hospital stay was 10 days (SD 3.8) vs. 11.4 days (SD 3.8) in the control. None of the patients in the intervention group and two in the control group needed revision surgery. Conclusions: Overall, 3D-navigated trans-sacral bar osteosynthesis seems to be a promising technique, enabling an accurate implant positioning while offering a low complication rate with an excellent short-term outcome in elderly patients with fragility fractures of the sacrum.